Drivers of COVID-19 vaccine uptake among rural populations in Madagascar: a cross-sectional study - Irina Kislaya; Diavolana Koecher Andrianarimanana; Valentina Marchese; Lalatiana Hosay; Rakotonavalona Rivomalala; Ramananjanahary Holinirina; Tahinamandranto Rasamoelina; Alexina Olivasoa Tsiky Zafinimampera; Sonya Ratefiarisoa; Olivette Totofotsy; Rivo Rakotomalala; Pia Rausche; et al. (BMC, 2024)
Abstract Background The WHO set the global immunisation threshold for COVID-19 at 70% to achieve worldwide protection against the disease. To date, global COVID-19 vaccine coverage is still below this threshold, in particular in several sub-Saharan African (SSA) countries, such as Madagascar. While factors influencing COVID-19 vaccine hesitancy have been widely explored in the past few years, research on drivers of COVID-19 vaccine uptake remains scarce. This study aimed at investigating drivers associated with COVID-19 vaccine uptake in the Boeny region of Madagascar. Methods The study used a cross-sectional survey design to collect data on drivers of vaccine uptake from a sample of adults recruited from 12 healthcare facilities between November 2022 and February 2023. Relative and absolute frequencies were used to summarize participants' characteristics. Prevalence ratios were estimated by Poisson regression to identify and compare sociodemographic and motivational drivers of vaccine uptake among those who were willing to get vaccinated against COVID-19 with those who had already been vaccinated. Results A total of 928 participants aged between 18 and 76 years were included in the study. Among those recruited, 44.9% (n = 417) had already been vaccinated and 55.1% (n = 511) were willing to receive their first dose of COVID-19 vaccine on the day of the interview. The proportions of those respondents who live in urban areas (56.5% vs. 43.8%) and who have high school or university education (46.6% vs. 35.8%) were higher for the uptake group, whereas the proportion of employed respondents (66.3% vs. 56.5%) was higher among those willing to get vaccinated. Vaccine being free of charge (aPR = 1.77 [CI 95%: 1.45-2.17]) and being able to travel again (aPR = 1.61 [CI 95%: 1.30-1.98]) were the drivers most strongly associated with higher vaccine uptake after adjustment for sociodemographic factors. Conclusions This study shows that actual COVID-19 vaccine uptake is influenced by a different set of factors than willingness to get vaccinated. Taking this difference in drivers into account can inform more tailored vaccination strategies to increase worldwide coverage.